Protective effect of saffron extract against doxorubicin cardiotoxicity in isolated rabbit heart. (3rd September 2013) - Chahine, Nathalie; Hanna, Jean; Makhlouf, Hassane; Duca, Laurent; Martiny, Laurent; Chahine, Ramez
Abstract: Context : Anticancer treatments such as anthracyclines are effective; however, they induce cardiotoxicity by releasing radical oxygen species (ROS). Saffron ( Crocus sativus ; Iridaceae) is a widely used spice with antioxidant properties and numerous health benefits that may provide cardioprotection. Objective : To assess the effect of saffron against acute myocardium damage by anthracyclines compared with electrolysis as a free radical generating system. Materials and methods : According to the Langendorff method, we used the model of an isolated rabbit heart perfused in retrograde. In one set of experiments, ROS was generated by electrolysis of the perfused heart solution (3 mA for 30 min) in the presence and absence of saffron extracts at the optimal dose (10 μg/ml). In another set, we perfused the heart with anthracycline, i.e. 30 μM doxorubicin (Doxo) in the presence and absence of 10 μg/ml saffron extracts. We evaluated cardiodynamics, as well as biochemical and pathological parameters, to emphasize the effectiveness of the treatment with saffron extract using the optimal dose of catalase (150 IU) as a positive control. Results : ROS generated, respectively, by electrolysis and by Doxo significantly ( p < 0.05) affects cardiovascular function; it decreased ventricular pressure (45.02 and 40.41%), heart rate (36.31 and 22.39%) and coronary flow (50.98 and 36.67%). Increased lipid peroxidation of the myocardium was also observed (118.22 and 56.58%), while superoxide dismutase activity decreased (48.33 and 38.70%). The myocardial architecture was altered and the intercellular spaces increased. Conclusion : Saffron perfused during electrolysis helps trap ROS and significantly improves myocardial function; however, saffron was less effective against Doxo, thus suggesting that mechanisms other than oxidative stress underlie Doxo cardiotoxicity.